Preference evaluation and perceived sensory comparison of fluticasone furoate and mometasone furoate intranasal sprays in allergic rhinitis. Issue 3 (June 2016) - Yonezaki, Masafumi; Akiyama, Kosuke; Karaki, Masayuki; Goto, Rieko; Inamoto, Rhyuhei; Samukawa, Yasushi; Kobayashi, Ryuichi; Kobayashi, Eiji; Hoshikawa, Hiroshi
Abstract: Objective: Intranasal corticosteroid sprays (INCSs) are commonly used for therapy of allergic rhinitis (AR). Adherence to regular use of INCSs is influenced by patient perception and preferences of products. The study objective was to compare perceived sensory attributes of fluticasone furoate nasal spray (FFNS) and mometasone furoate nasal spray (MFNS) in AR patients. Methods: In a multicenter, randomized, crossover, prospective study, 40 seasonal AR patients were administered both FFNS and MFNS for 2 weeks each in a crossover fashion, for a total of 4 weeks. Patients completed questionnaires for each product regarding perceived sensory attributes at the end of each two-week period of product administration. Results: FFNS was significantly preferred over MFNS. Significantly, fewer subjects perceived a bitter taste ( p = 0.01), medication running down their throat ( p = 0.033), and medication running out of their nose ( p = 0.002) with FFNS. MFNS was more frequently reported to induce nasal irritation ( p = 0.012), sneezing ( p = 0.017), and rhinorrhea ( p = 0.007) compared to FFNS. Interestingly, these findings were markedly observed in females. Medicine dripping out of the nose and nasal shooting were the most common problems reported for MFNS with a higher proportion of subjects who felt moderate-to-severe discomfort. Overall, 52.5% of patients expressed a preference for FFNS compared with 22.5% for MFNS. Conclusion: Several perceived sensory attributes of FFNS were rated significantly superior to MFNS. FFNS may contribute to enhanced treatment outcomes in AR patients due to improved treatment adherence.